Respuesta :
Answers and Step-by-step explanations:
9. Subtract root x from both sides: [tex]\sqrt{x+12} =6-\sqrt{x}[/tex]
Square both sides: x + 12 = 36 - 12[tex]\sqrt{x}[/tex] + x
Subtract x and 36 from both sides: -24 = -12[tex]\sqrt{x}[/tex]
Divide both sides by -12: 2 = [tex]\sqrt{x}[/tex]
Square both sides again: x = 4
10. Switch the places of the two root expressions: [tex]\sqrt{4x-1} =1-2\sqrt{x}[/tex]
Square both sides: 4x - 1 = 1 - 4[tex]\sqrt{x}[/tex] + 4x
Subtract 4x and 1 from both sides: -2 = -4[tex]\sqrt{x}[/tex]
Divide by -4 from both sides: 1/2 = [tex]\sqrt{x}[/tex]
Square both sides again: x = 1/4
11. Square both sides: 4x^2 = 4x - 1
Move all the terms to one side: 4x^2 - 4x + 1 = 0
Factorize: (2x - 1)(2x - 1) = 0 ⇒ x = 1/2
12. Square both sides: 4x - 1 = 4 - 8x + 4x^2
Move all the terms to one side: 4x^2 - 12x + 5 = 0
(2x - 5)(2x - 1) = 0 ⇒ x = 5/2 or x = 1/2
Hope this helps!
Answer:
9. x = 4
10. x = ¼
11. x = ½
12. x = ½
Step-by-step explanation:
9. sqrt(x + 12) = 6 - sqrt(x)
Square both sides
x + 12 = 36 - 12sqrt(x) + x
12sqrt(x) = 24
sqrt(x) = 2
x = 4
10. 2sqrt(x) = 1 - sqrt(4x - 1)
Square both sides
4x = 1 - 2sqrt(4x - 1) + 4x - 1
-2sqrt(4x - 1) = 0
sqrt(4x - 1) = 0
4x - 1 = 0
x = ¼
11. 2x = sqrt(4x - 1)
4x² = 4x - 1
4x² - 4x + 1 = 0
4x² - 2x - 2x + 1 = 0
2x(2x - 1) - (2x - 1) = 0
(2x - 1)(2x - 1) = 0
x = ½
12. sqrt(4x - 1) = 2 - 2x
4x - 1 = (2 - 2x)²
4x - 1 = 4 - 8x + 4x²
4x² - 12x + 5 = 0
4x² - 2x - 10x + 5 = 0
2x(2x - 1) - 5(2x + 1) = 0
(2x - 1)(2x - 5) = 0
x = ½ , 5/2
x = 2.5 is rejected because it doesn't satisfy the equation
* when solving equations involving radicals, make sure to verify your answers by plugging in the values in the initial equation